Small island economies - Worrell, DeLisle (Praeger New YorkUS, 1987)
Gives overview of Caribbean economies describing their products, trading partners, levels of development, and selected institutional features. Discusses commodity price trends, financial market changes and other aspects of the world environment as they affect the Caribbean. Contains a chapter each on country performance of Barbados, Guyana, Jamaica, Trinidad and Tobago and the remaining English-speaking countries. In each case discusses the prospects in 1970, the subsequent performance, the economic consequences of world economic instability and the policy response. Discusses regional economic association and integration and concludes with a discussion on adjustment policies in small open economies noting important lessons.